(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of the present research is to measure the degree of strategic effectiveness (fahs) in the development of grammar skills of high school students in the Kingdom of Saudi Arabia and to achieve the goal of the researcher the researcher used the semi-experimental approach; On ten arbitrators specializing in grammar, morphology, curricula and methods of teaching the Arabic language. After confirming the validity of the guideline, the researcher prepared an achievement test consisting of (22) paragraphs of the type of short answer and multiple choice. The researcher trained a teacher to apply the strategy to the experimental research sample using the (screening) component of (30) students, and the same parameter taught the control sample of (30) students using the units method prescribed in the textbook. The results showed that there were statistically significant differences at (0α0.05) level between the mean scores of the experimental and control group in the post application of the achievement test in favor of the experimental group. The effect size of the reading skill was (0.398) and (0.264) for the analysis skill. Therefore, the researcher recommends the training of Arabic language teachers in using the strategy (fahs) when teaching grammar rules and experimenting with them in teaching the rules of rhetoric and spelling as well as experimenting with teaching the laws of mathematics and physics courses in all stages of education.